2008
DOI: 10.1037/0012-1649.44.1.286
|View full text |Cite
|
Sign up to set email alerts
|

Social risk and protective factors for African American children's academic achievement and adjustment during the transition to middle school.

Abstract: The transition to middle school is often marked by decreased academic achievement and increased emotional stress, and African American children exposed to social risk may be especially vulnerable during this transition. To identify mediators and protective factors, the authors related severity and timing of risk exposure to academic achievement and adjustment between 4th and 6th grade in 74 African American children. Longitudinal analyses indicated that severity more than timing of risk exposure was negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
1
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 106 publications
8
119
1
17
Order By: Relevance
“…Additionally, in one of the few studies to examine these relationships longitudinally, Wong and colleagues (2003) found that experiences with teacher and peer discrimination at school lessened achievement motivation and academic outcomes as well as the increased likelihood of problem behaviors in African American adolescents. Additional research has also demonstrated the deleterious impact on race discrimination experiences on academic-related outcomes (e.g., Burchinal, Roberts, Zeisel, & Rowley, 2008;Eccles et al, 2006;Neblett, Philip, Cogburn & Sellers, 2006;Powell & Arriola, 2003;Smalls, White, Chavous, & Sellers, 2007;Thomas, Caldwell, Faison & Jackson, 2009). Taken together, this research provides some evidence that discrimination, prejudice and other disadvantages in school settings is associated with negative educational outcomes among African American adolescents.…”
Section: Racial Climate and Achievement Outcomesmentioning
confidence: 69%
“…Additionally, in one of the few studies to examine these relationships longitudinally, Wong and colleagues (2003) found that experiences with teacher and peer discrimination at school lessened achievement motivation and academic outcomes as well as the increased likelihood of problem behaviors in African American adolescents. Additional research has also demonstrated the deleterious impact on race discrimination experiences on academic-related outcomes (e.g., Burchinal, Roberts, Zeisel, & Rowley, 2008;Eccles et al, 2006;Neblett, Philip, Cogburn & Sellers, 2006;Powell & Arriola, 2003;Smalls, White, Chavous, & Sellers, 2007;Thomas, Caldwell, Faison & Jackson, 2009). Taken together, this research provides some evidence that discrimination, prejudice and other disadvantages in school settings is associated with negative educational outcomes among African American adolescents.…”
Section: Racial Climate and Achievement Outcomesmentioning
confidence: 69%
“…No único estudo que incluiu em seu modelo de análise fatores de proteção em interação com fatores de risco, a estratégia se mostrou frutífera para identificar a influência atenuante das práticas parentais positivas sobre a manifestação dos problemas na adolescência (Latimer et al, 2003), um resultado que se alinha aos de um estudo recente com foco na transição para o ensino médio (Burchinal, Roberts, Zeisel, & Rowley, 2008). É importante, então, registrar a necessidade de maior investimento de pesquisa na exploração das condições de proteção do ambiente, não só para melhor conhecimento dos processos envolvidos no curso dos problemas em foco, mas, também, pela potencial contribuição para programas de prevenção.…”
Section: Estudos Sobre Precursores Da Associação Entre Problemas De Cunclassified
“…휴대전화 중독은 충 동성과 상관관계가 있고, 휴대전화 중독 청소년에서 충 동성이 높은 것으로 나타났다 [19]. 이와 같이 충동성은 자기통제가 결여된 상태 [20]로 청소년에서 충동성을 통 제하지 못하면 문제행동이 발생한다 [21]. 충동성은 조 절을 통해 중독을 예방 할 수 있기 때문에 [22] …”
Section: 휴대전화 중독은 휴대전화를 사용하지 않으면 불안unclassified